Implementasi Kompetensi Pedagogik Instruktur Dalam Meningkatkan Kesiapan Kerja Peserta Pelatihan Di UPTD Balai Latihan Kerja Kota Bogor - Nur Dea Utami; Suherman Suherman; Mochamad Naim (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to describe the implementation of the instructor's pedagogical competence at UPTD Balai Latihan Kerja Bogor City. The method used is descriptive method on qualitative approach, data sources used primary data sources and secondary data sources, data collection techniques are interviews and observations, data analysis techniques are data reduction, data presentation and data verification. The results of this study are the pedagogical competence of instructors at the UPTD Balai Latihan Kerja Kota Bogor can be said to be good, this is evidenced by the instructors applying their pedagogical competence, the implementation of the instructor's pedagogical competence can be said to be successful and the work readiness of trainees at the UPTD Balai Latihan Kerja Kota Bogor can be said to be optimal.